Isolation and Characterization of Enterococcus faecalis-Infecting Bacteriophages From Different Cheese Types - del Rio, Beatriz; Sánchez-Llana, Esther; Martínez, Noelia; Fernández, María; Ladero, Victor; Alvarez, Miguel A. (Frontiers in Microbiology, 2021)
Enterococci are a diverse group of Gram-positive, lactic acid bacteria (LAB). They are found in many environments, including fermented foods, the organoleptic characteristics of which are influenced by their metabolism. However, these microorganisms constitute a health threat may since they also produce biogenic amines (BAs) at high concentrations, in these foods, the consumption of which can lead to intoxication. Enterococcus faecalis has been identified as the main producer of the BAs tyramine and putrescine in cheese. Moreover, this bacterium has also emerged as an important hospital-acquired pathogen via its acquisition of antimicrobial resistance. Bacteriophages possess features that make them optimal biotechnological weapons for controlling bacterial growth in disease and food spoilage contexts. However, no silver bullet bacteriophage exists that can eliminate all the undesirable bacteria in a complex environment. This is particularly true for LAB species; phages infecting these species usually have a very narrow host range. Rather, a combination of phages with different host ranges would be required. This work reports the isolation of several E. faecalis-infecting bacteriophages from different types of cheese, along with the range of E. faecalis strains of diverse origin (from dairy to clinical environments) they are able to infect. Some of these phages were subjected to morphological and genomic characterization which confirmed their belonging to different families and genera. The present findings increase the potential arsenal for the bacteriophage-based biocontrol of harmful E. faecalis populations.